We the animals - Torres, Justin 1980- (Mariner Books, 2012)
"An exquisite, blistering debut novel. Three brothers tear their way through childhood-- smashing tomatoes all over each other, building kites from trash, hiding out when their parents do battle, tiptoeing around the house as their mother sleeps off her graveyard shift. Paps and Ma are from Brooklyn--he's Puerto Rican, she's white--and their love is a serious, dangerous thing that makes and unmakes a family many times. Life in this family is fierce and absorbing, full of chaos and heartbreak and the euphoria of belonging completely to one another. From the intense familial unity felt by a child to the profound alienation he endures as he begins to see the world, this beautiful novel reinvents the coming-of-age story in a way that is sly and punch-in-the-stomach powerful. Written in magical language with unforgettable images, this is a stunning exploration of the viscerally charged landscape of growing up, how deeply we are formed by our earliest bonds, and how we are ultimately propelled at escape velocity toward our futures"--Provided by publisher